Mass Spectral Studies of 6-Cinnamoyl Chromones - PRABHA SHARMA, VINAY; V. SINGH, OM (Asian Journal of Chemistry, 2010)
Mass spectral fragmentation modes of 6-cinnamoyl chromones constitute subject matter of this publication which have exhibited a definite pattern of fragmentation. These studies were carried out to provide additional support to the structures assigned to compounds.